THE RELATIONSHIP BETWEEN SOCIAL MEDIA ADVERTISING AND SKIN CARE SELECTION AMONG COLLEGE STUDENTS - Yudi Budianto (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The rapid development of social media has changed consumption patterns, including in the skin care industry, where students have become one of the most active and vulnerable market segments to the influence of digital advertising. The general objective of this study is to determine the relationship between social media advertising and skin care product selection among students. This study is a quantitative analytical research using a cross-sectional approach with a sample size of 43 students. The variables studied are presented in the form of frequency distribution tables and tested using univariate and bivariate analysis, specifically through a questionnaire instrument. The results of the chi-square test yielded a ρ value of 0.007, indicating a significant relationship between online social media advertising and skin care product selection among female students in the DIII Nursing Program at STIKES Al-Ma'arif Baturaja. The results of the chi-square test yielded a ρ value of 0.013, indicating a relationship between offline media advertisements and the selection of skin care products among female students in the DIII Nursing Program at STIKES Al-Ma'arif Baturaja. The conclusion of this study is that there is a relationship between social media advertisements and the selection of skin care products among female students in the DIII Nursing Program at STIKES Al-Ma'arif Baturaja.